Does remote work reinforce gender gaps in (un)paid labor? - Jean-Victor Alipour (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
I study how the rise in working from home (WFH) affects the gender division of paid and unpaid labor (caregiving, domestic tasks). Identification uses differences in individuals' exposure to the Covid-induced WFH shock, measured by the WFH feasibility of their job in 2019. Using panel data from the German SOEP, I estimate 2SLS models that instrument realized WFH in 2022 with WFH feasibility. Results show that WFH reduces paid hours and increases domestic work and leisure (including sleep) among women. Men's time use remains largely unchanged, partly because WFH induces moves toward larger, more distant homes, offsetting commuting time savings. Within-couple analyses confirm that the Big Shift to WFH intensifies gender gaps in paid and unpaid work, particularly caregiving. I find that gender norms, bargaining power, and childcare demands interact with WFH in ways that reinforce the unequal division of labor.
Keywords: J16; J22; J13; 330; work from home; time use; unpaid work; division of labor; gender norms; bargaining power